Better Usability and Technical Stability Could Lead to Better Work-Related Well-Being among Physicians - Vainiomäki, Suvi; Aalto, Anna-Mari; Lääveri, Tinja; Sinervo, Timo; Elovainio, Marko; Mäntyselkä, Pekka; Hyppönen, Hannele (Applied Clinical Informatics, 2017)
Background and Objective Finnish physicians have been increasingly dissatisfied with poor usability of the electronic patient record (EPR) systems, which they have identified as an overload factor in their work. Our aim is to specify which factors in EPRs are associated with work-related well-being of physicians.Methods A web-based questionnaire was sent to Finnish physicians younger than 65 years; the responses (n = 3,781) represent one-fourth of these. This was a repetition of a survey in 2010, where this questionnaire was used for the first time. In addition to statements assessing usability, there were questions measuring time pressure and job control. The relation between usability and work well-being was investigated with hierarchical multivariate regression analyses: With time pressure and job control as dependent variables, EPR usability assessments and physicians' background information were used as independent variables.Results In the multivariate analyses, technical problems that are often experienced in the EPR were related to higher time pressure and lower job control. Active participation in the development of the EPR system was related to stronger time pressure and stronger job control. In addition, use of several systems daily and the experience of time-consuming documentation of patient information for statistical purposes (billing, national registries, and reporting) were related to higher time pressure, while those with longer experience with the EPR system and those experiencing easy-to-read nursing records reported higher job control.Conclusion To relieve time pressure and increase sense of job control experienced by physicians, usability, integrations, and stability of the EPR systems should be improved: fewer login procedures, easier readability of nursing records, and decreased need for separate documentation for statistical purposes. Physician participation in the EPR development would increase the feeling of job control, but would add the time pressure. Hence, time for developmental work should be arranged.
Keywords: electronic patient records and systems; patient records; specific software; clinical IT systems; usability; workflows